Meta-Analysis of qPCR for Bovine Respiratory Disease Based on MIQE Guidelines - Barnewall, Rebecca J.; Marsh, Ian B.; Quinn, Jane C. (Frontiers in Molecular Biosciences, 2022)
Qualitative and quantitative PCR-based tests are widely used in both diagnostics and research to assess the prevalence of disease-causing pathogens in veterinary medicine. The efficacy of these tests, usually measured in terms of sensitivity and specificity, is critical in confirming or excluding a clinical diagnosis. We undertook a meta-analysis to assess the inherent value of published PCR diagnostic approaches used to confirm and quantify bacteria and viruses associated with bovine respiratory disease (BRD) in cattle. This review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A thorough search of nine electronic databases (Web of Science, EBSCOhost, Cambridge journals online, ProQuest, PubMed, Sage journals online, ScienceDirect, Wiley online library and MEDLINE) was undertaken to find studies that had reported on the use of PCR and/or qPCR for the detection and/or quantification of BRD associated organisms. Fourteen studies meeting the inclusion criteria for reporting quantitative PCR for identification of BRD associated microorganisms were included in the analysis. Each report was assessed on reporting against the Minimum Information for Publication of Quantitative Real-Time PCR Experiment (MIQE) and PCR primer/probe sequences extracted for in silico specificity testing. Results showed that 79% of the analysed articles did not report the application of the MIQE guidelines in their study. High stringency in silico testing of 144 previously published PCR primer/probe sequences found many to have variable specificity. Although this analysis was only applied to one specific disease state, there appears to be more broadly a need for veterinary diagnostic studies to adopt international best practice for reporting of quantitative PCR diagnostic data in order to be both accurate and comparable between studies and methodologies.